The Effect of Core Training on Fitness, Trunk Isokinetic Muscular Function, and Body-Composition in Boxing Athletes - Sung-Ho Ahn; Jin-Seok Lee; Chang-Gyun Kim (Asian Society of Kinesiology, 2018)
OBJECTIVES The purpose of this study was to investigate the effect of core training on boxer's fitness, trunk insokinetic muscular function, and body-composition. METHODS Sixteen boxing athletes participated in two trials: (1) core training, and (2) control. Fitness factors, trunk isokinetic muscular function, and body composition measurements were performed at pre (0 week), post (8 weeks). RESULTS Core training was effective in improving trunk flexion, single leg stance, whole body reaction time, grip strength in post-test than in pre-test. Also, was effective in improving 30°/sec peak torque of flexor, 120°/sec mean torque of extensor in post-test than in pre-test. Core raining increased body weight and body fat mass. CONCLUSIONS These suggest that core training can have a positive impact on the performance of boxers.